If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4x + -2) + -2x = 2x + -2 Reorder the terms: 2(-2 + 4x) + -2x = 2x + -2 (-2 * 2 + 4x * 2) + -2x = 2x + -2 (-4 + 8x) + -2x = 2x + -2 Combine like terms: 8x + -2x = 6x -4 + 6x = 2x + -2 Reorder the terms: -4 + 6x = -2 + 2x Solving -4 + 6x = -2 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -4 + 6x + -2x = -2 + 2x + -2x Combine like terms: 6x + -2x = 4x -4 + 4x = -2 + 2x + -2x Combine like terms: 2x + -2x = 0 -4 + 4x = -2 + 0 -4 + 4x = -2 Add '4' to each side of the equation. -4 + 4 + 4x = -2 + 4 Combine like terms: -4 + 4 = 0 0 + 4x = -2 + 4 4x = -2 + 4 Combine like terms: -2 + 4 = 2 4x = 2 Divide each side by '4'. x = 0.5 Simplifying x = 0.5
| 4y+3=7y | | y=-3-4+5 | | 4h-2h+3=2h+2h | | -9x+x^2=-9 | | -7m+3=31 | | 0.3x-0.5(3-x)=1.3 | | -9x+x^2=9 | | 2s+4b=12 | | 436.6+.37Y=Y | | -5(4p+3)-37=4(3p+3) | | 10y=6y+8 | | 4x^3+4x^2+16x=0 | | 5x-3=-9 | | 18x=54.198 | | 7(c-5)=8(c-6) | | Y-17=11 | | 9=x(9-x) | | -15+8x=8x-8 | | .25x-6=12 | | 9-(2+3)=2(6-2) | | 6+-5n+2n=33+-96 | | 100=25-7.5d | | 3(x+4)+2x=4x+14 | | 2.5x-6=12 | | C+2=3c+9 | | 8.08=-11402x^2+766.68x-6.6669 | | -81x^2+4=0 | | W-9c=8forw | | 3=4(5+6n) | | 6-5n+2n=3-96 | | X^2-5x=864 | | 1.33x-5=7 |